Case Report: a novel homozygous ASNS variant in a Chinese female with severe microcephaly, encephalopathy and epilepsy - Cheng, Shuangxi; Zhang, Fang; Wang, Qingming; Zhang, Jianfei; Lyu, Guizhen; Li, Yanwei; Zhou, Xinlong; Yuan, Haiming (Frontiers in Neuroscience, 2025)
Asparagine synthetase deficiency (ASNSD; OMIM# 615574) is a severe autosomal recessive neurodevelopmental disorder caused by biallelic pathogenic variants in ASNS (OMIM# 108370). Clinical features of ASNSD include congenital microcephaly, profound psychomotor impairment, progressive encephalopathy, refractory epilepsy, and characteristic neuroimaging abnormalities. Since its initial description, approximately 100 cases have been documented worldwide with 60 distinct ASNS variants reported. Here, we report a Chinese patient with prenatal microcephaly, intrauterine growth retardation (IUGR) and reduced middle cerebral artery blood flow velocity. Postnatally, she presented with progressive microcephaly, profound psychomotor delay and intractable epilepsy. Brain MRI showed corpus callosum hypoplasia, cerebellar hypoplasia, delayed myelination, cortical atrophy, enlarged ventricles and gyral simplification. Whole-exome sequencing (WES) was applied to detect the causative variants and identified a novel homozygous variant c.4 T > G (p.Cys2Gly), in ASNS in our patient that was inherited from the heterozygous unaffected parents. Our report contributes to the expanding genotypic and prenatal phenotype spectrum of ASNSD.